Faktor Yang Mempengaruhi Kepatuhan Pajak UMKM Sektor Kuliner Di Kota Bengkulu - Aisyah Meutia Amanda; Edo Mardiansya; Munti Metralia; Winny Lian Seventeen (Media Akuntansi Perpajakan, 2026)
This study aims to analyze the factors influencing tax compliance among culinary Micro, Small, and Medium Enterprises (MSMEs) in Bengkulu City. The independent variables examined include tax knowledge, taxpayer awareness, tax sanctions, and tax authority services, while tax compliance serves as the dependent variable. This research employed a quantitative approach with an associative design. Data were collected through questionnaires distributed to 105 culinary MSME owners selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that tax knowledge, tax sanctions, and tax authority services have a positive and significant effect on MSME tax compliance, whereas taxpayer awareness does not have a significant effect. Simultaneously, all independent variables significantly influence tax compliance, with an Adjusted R Square value of 0.671, indicating that 67.1% of the variation in tax compliance can be explained by the proposed model. These findings imply that efforts to improve MSME tax compliance should prioritize enhancing tax education, strengthening the consistent enforcement of tax sanctions, and improving the quality of tax authority services.